FACTORS RELATED TO BPJS KESEHATAN PARTICIPATION IN TRADERS AMONG TRADERS - Darmawansyah; Muzhaffar, Zaky; Suci Rahmadani (Universitas Islam Negeri Alauddin Makassar, 2023)
Background: BPJS Kesehatan plans for Universal Health Coverage in Indonesia to reach 98% in accordance with the National Medium-Term Development Plan (RPJMN). Objective: This study aims to determine the factors associated with BPJS Health membership among traders in Pa'baeng-baeng Marketplace, Makassar City in 2023. Method: This research is a quantitative study using a cross-sectional study design. The population in this study were 370 traders with a sample size of 160 traders. The sampling technique used was accidental sampling conducted at Pa'baeng-baeng Marketplace, Makassar City. Statistical tests using the chi-square test. Result: The results showed that the factors that influence the participation of traders in BPJS Kesehatan are income (p=0.043), ability to buy (p=0.013), perception (p=0.000), and family support (p=0.000). Variables that are not associated with the participation of traders in BPJS Kesehatan are education variables (p=0.676) and the number of family members (p=0.563). Conclusion: The conclusion of this study is that there is an influence between income, ability to buy, perceptions, and family support with BPJS Health participation among traders in Pa'baeng-baeng Marketplace, Makassar City in 2023.